2019
DOI: 10.1101/737395
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TGFβ regulation of perilacunar/canalicular remodeling is sexually dimorphic

Abstract: 1.AbstractBone fragility is the product of defects in bone mass and bone quality, both of which show sex-specific differences. Despite this, the cellular and molecular mechanisms underpinning the sexually dimorphic control of bone quality remain unclear, limiting our ability to effectively prevent fractures, especially in postmenopausal osteoporosis. Recently, using male mice, we found that systemic or osteocyte-intrinsic inhibition of TGFβ signaling, a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…OA is more prevalent in women than in men, particularly after menopause, demonstrating a need to better understand the sex-specific pathogenesis of OA (44). We have recently shown that osteocytic TGFβ signaling induces PLR in a sex-specific manner (28). While male TβRII ocy−/− mice demonstrate hallmarks of suppressed PLR in the cortical bone, including blunted canalicular networks, reduced expression of PLR enzymes, and defective bone quality, PLR and bone quality remain intact in female TβRII ocy−/− mice (28).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…OA is more prevalent in women than in men, particularly after menopause, demonstrating a need to better understand the sex-specific pathogenesis of OA (44). We have recently shown that osteocytic TGFβ signaling induces PLR in a sex-specific manner (28). While male TβRII ocy−/− mice demonstrate hallmarks of suppressed PLR in the cortical bone, including blunted canalicular networks, reduced expression of PLR enzymes, and defective bone quality, PLR and bone quality remain intact in female TβRII ocy−/− mice (28).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that osteocytic TGFβ signaling induces PLR in a sex-specific manner (28). While male TβRII ocy−/− mice demonstrate hallmarks of suppressed PLR in the cortical bone, including blunted canalicular networks, reduced expression of PLR enzymes, and defective bone quality, PLR and bone quality remain intact in female TβRII ocy−/− mice (28). This set of observations remained true in this study, where 16-week-old male TβRII ocy−/− mice showed a disruption of the subchondral bone canalicular network, increased SBP | 423 thickness, and signs of worsened joint degeneration, while female TβRII ocy−/− mice did not, demonstrating that the sexually dimorphic role of osteocytic TGFβ signaling extends to the joint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations